Application of Lean Methodologies in a Neurosurgery High Dependency Unit - Esteves, Ricardo Balau (IntechOpen, 2016)
This study aims to apply Lean methodologies at a neurosurgery high dependency unit (NHDU) for increasing safety and quality on the care delivered to acute neuropatients and to reduce time, steps, and distance travelled by nurses accessing life support equipment (LSE). The methodology used in this study is an action research, supported by a longitudinal mixed method approach with a one‐group within‐subjects pretest‐posttest experimental type design. Resulting in a high waste of time, steps, and distance travelled to reach them. After the application of Lean methodologies, distance, steps, and time travelled by Nurses were quite improved. Lean methodologies applied in NHDU contributed to improve the organization, availability, and accessibility of LSE by putting them at the point‐of‐use. Quality and safety of patient care were also improved by allowing almost immediate life support interventions. Resistance to change was the major limitation. The Lean philosophy empowers health facility managers with tools and methodologies that help them create health gains, implement a culture of continuous improvement of care and working environment, identify and eliminate barriers, and waste that limits the work of staff in providing quality services and saving lives. This chapter highlights the responsibility of health facility managers to properly organize health units to cope with emergency situations, by allowing immediate, efficient, and effective intervention of staff.